Factors affecting Oithona nana and Oithona similis along a salinity gradient - ANNABI-TRABELSI, NEILA; KOBBI-REBAI, RAYDA; AL-ENEZI, YOUSEF; ALI, MOHAMMAD; SUBRAHMANYAM, M.N.V; BELMONTE, GENUARIO; AYADI, HABIB (Mediterranean Marine Science, 2021)
Spatial and temporal variations of reproduction variables of the two cyclopoid copepods Oithona nana Giesbrecht, 1893 and Oithona similis Claus, 1866 were evaluated monthly from September 2007 to August 2008 in four ponds at different salinities in the solar saltern of Sfax, Tunisia, under hypersaline conditions. Along the salinity gradient the abundance of O. nana and O. similis declined from 14,900 ± 15,200 ind. m-3 (A1) to 6,800 ± 7,200 (C31) and from 13,800 ± 17,100 ind. m-3 (A1) to 3,700 ± 5,800 (C31), respectively. The findings showed that the abundance of these Oithona species, particularly the ovigerous females, was positively correlated with the abundance of Diatomeae, and negatively correlated with salinity. The egg production rate (EPR), the egg diameter, the clutch size, as well as the cephalothorax length of mature females, were all negatively correlated with salinity and positively correlated with the abundance of Diatomeae. Along the existing salinity gradient, the EPR decreased from 4.7 ± 0.39 (A1) to 3.2 ± 0.13 (C31) eggs female-1 day-1 and from 5.19 ± 0.46 (A1) to 3.66 ± 0.05 (C31) eggs female-1 day-1 for O. nana and O. similis, respectively, and this could mainly be attributed to the hypersaline conditions. The positive relationship between the abundance of Diatomeae with all traits shows, that these may be a vital component of the diet for the investigated species. The reduction of body size of Oithona along the salinity gradient demonstrates that such a character could mainly be due to a network of causes, related with the confinement and not only to salinity.